Blockade of uptake for dopamine, but not norepinephrine or 5-HT, increases selection of high effort instrumental activity: Implications for treatment of effort-related motivational symptoms in psychopathology. (October 2016) - Yohn, Samantha E.; Errante, Emily E.; Rosenbloom-Snow, Aaron; Somerville, Matthew; Rowland, Margaret; Tokarski, Kristin; Zafar, Nadia; Correa, Merce; Salamone, John D.
Abstract: Deficits in behavioral activation, exertion of effort, and other psychomotor/motivational symptoms are frequently seen in people with depression and other disorders. Depressed people show a decision bias towards selection of low effort activities, and animal tests of effort-related decision making are being used as models of motivational dysfunctions seen in psychopathology. The present studies investigated the ability of drugs that block dopamine transport (DAT), norepinephrine transport (NET), and serotonin transport (SERT) to modulate work output in rats responding on a test of effort-related decision making (i.e., a progressive ratio (PROG)/chow feeding choice task). With this task, rats choose between working for a preferred food (high carbohydrate pellets) by lever pressing on a PROG schedule vs. obtaining a less preferred lab chow that is freely available in the chamber. The present studies focused on the effects of the selective DAT inhibitor GBR12909, the selective SERT inhibitor fluoxetine, and the selective NET inhibitors desipramine and atomoxetine. Acute and repeated administration of GBR12909 shifted choice behavior, increasing measures of PROG lever pressing but decreasing chow intake. In contrast, fluoxetine, desipramine and atomoxetine failed to increase lever pressing output, and actually decreased it at higher doses. In the behaviorally effective dose range, GBR12909 elevated extracellular dopamine levels in accumbens core as measured by microdialysis, but fluoxetine, desipramine and atomoxetine decreased extracellular dopamine. Thus, blockade of DAT increases selection of the high effort instrumental activity, while inhibition of SERT or NET does not. These results have implications for the use of monoamine uptake inhibitors for the treatment of effort-related psychiatric symptoms in humans. Highlights: Effort-related choice tasks can be used to assess motivational effects of drugs. Rats were assessed using a progressive ratio/chow feeding choice task. The dopamine transport blocker GBR12909 increases exertion of effort. Blockers of 5-HT and norepinephrine transport do not. These results have implications for treating human motivational symptoms.